The Existential Cost of the Social Staging of Life: Man in an Ontological Trap - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
In the article, the problems of the incompleteness of human eхistence and the specificity of social ontology are discussed in the context of тhe social project. Social ontology is a complete system endowed with the «constitutional» powers of organizing human coexistence, as well as regulating economic, political and socio-cultural life,within which human natural and metaphysical identities constantly clash.The problem is that only by passing from the «biological economy” to the «metaphysical economy» can a person confirm his ontological greatness, acquire a metaphysical identity and become a social subject․ But in order for a person to acquire the status of a social subject, he must identify with the role assigned to him and be what the given social system wants him to be. In fact,in the social staging of life, existence is deprived of differences, because the players are not independent subjects, but puppet incarnations formed by order of the social system and subordinate to it,or, in other words, dead masks representing the subject. Additionally, in order to discover the manifestation charachteristics of the phenomena of ’’ the death of the subject’’ in the sociocultural context it is necessary to transition from the procedural consideration to the examination of the status (role) derived from the present social institutions, and to show that the role is not only the constitutive principle of human existence, but also a mask with the help og which one can present or hide the individuality of a person. This has already been done.